Retrospective cohort study on cumulative live birth rate of in vitro fertilization/intracytoplasmic sperm injection after multiple complete cycles in patients with diminished ovarian reserve - Sisi Xi; Xiuli Yang; Jing Shang; Qing Xue (BMC Pregnancy and Childbirth)
Abstract Background Diminished ovarian reserve refers to the decrease in the quantity and quality of oocytes in the ovary which may cause poor fertility outcomes even with the help of assisted reproductive techniques. Most patients will undergo multiple cycles of IVF treatments. Compared to the live birth rate of a single oocyte retrieval cycle, the cumulative live birth rate across multiple cycles provides a more comprehensive reflection of treatment efficiency and a patient’s long-term outcomes, holding the following importance for clinical decision-making. This study aimed to evaluate the cumulative live birth rate of in vitro fertilization / intracytoplasmic sperm injection after multiple complete cycles in patients with diminished ovarian reserve. Methods We performed a retrospective cohort study in female patients with diminished ovarian reserve undergoing in vitro fertilization / intracytoplasmic sperm injection cycle during the period from January 2016 to December 2020. All patients were followed up for 3 years until either discontinuation of treatments or delivery of one or more live infants. The conservative estimate of cumulative live birth rate and the optimal estimate of cumulative live birth rate were calculated. Results A total of 343 patients were included in this study, including 996 oocyte retrieval cycles. After one or more cycles of treatments, a total of 141 couples achieved live births during the study period, with a conservative estimate cumulative live birth rate of 41.1% and a optimistic estimate cumulative live birth rate of 81.0%. For women aged < 35 and 35 ~ 39, after 6 oocyte retrieval cycles, the conservative/optimistic estimates of the cumulative live birth rates reached 57.4/ 82.7% and 41.1/ 64.8%, respectively. For elderly women equal or over 40 years old, the conservative/optimistic estimates of the cumulative live birth rates after 6 oocyte retrieval cycles were only 14.7/ 26.0%. The multivariate analysis results showed that: age and the number of oocytes retrieved per cycle were significantly associated with live birth outcomes. Conclusion For female diminished ovarian reserve patients younger than 40 years old, multiple cycles in vitro fertilization / intracytoplasmic sperm injection treatments can help to achieve satisfactory success rates. As for elder patients aged 40 or above, more than 4 cycles of in vitro fertilization / intracytoplasmic sperm injection may have limited benefits.